PENGARUH SENSORY MARKETING, EXPERIENTIAL VALUE, DAN EMOTIONAL LABOR TERHADAP REPURCHASE INTENTION KONSUMEN WARUNG KOPI LOKAL DI KOTA SAMARINDA: PENDEKATAN MIXED METHODS DENGAN SEM-PLS - Pratama Putra, Hendra; El Umammi, Mayada Khaira; Agustinali, Agustinali; Rahmawati, Rahmawati (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2025)
This study examines the influence of sensory marketing, experiential value, and employee emotional labor on repurchase intention among consumers of local coffee shops (warung kopi) in Samarinda City, East Kalimantan. These three constructs represent an underexplored integrated framework, particularly within the MSME culinary context in eastern Indonesia. A mixed methods design with an explanatory sequential approach was employed, combining SEM-PLS as the dominant quantitative method (80%) with phenomenological in-depth interviews as the complementary qualitative method (20%). Survey data were collected from 215 respondents using a 5-point Likert scale structured questionnaire. SmartPLS 4.0 with 5,000 bootstrapping subsamples was applied. Results show that sensory marketing (?=0.341; p<0.001), experiential value (?=0.278; p<0.001), and deep acting (?=0.203; p=0.001) positively and significantly influence repurchase intention, while surface acting exerts a negative effect (?=?0.157; p=0.016). The model yields R²=0.769 and Q²=0.548, indicating strong predictive power. Qualitative findings reveal that authentic coffee aroma, acoustic ambience, service sincerity, and emotional experiential value are key determinants of repurchase intention. This study contributes to extending Stimulus-Organism-Response (S-O-R) theory within the local MSME culinary sector and provides strategic recommendations for warung kopi operators.